(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The government of South Africa does not have an economic development model that seeks to address poverty. Economic policies are not specifically developed to create employment opportunities but the main focus is on public service delivery. Job creation is not the primary objective of economic policies. This paper, therefore, focuses on the government's failures to develop a job creation model in South Africa that directly focus on job creation. Subsequently, job creation can be made possible if the economy of the country is well-balanced. The lack of political will and the leadership deficiencies in the country has contributed to the failure of the government to develop a job creation model. The study applied secondary research methodology and reached conclusions based on the existing data. The study found that a lot can be done if there is a political will to resolve the poverty and unemployment challenges. The study recommends that the leadership must be changed especially complacent leadership and replace them with visionary leaders.